Myanmar's Urbanization : Creating Opportunities for All - World Bank Group (World Bank, Washington, DC, 2019)
Urbanization in Myanmar is still in an early phase with slightly less than one-third of the population living in cities. This presents an enormous opportunity for the country. Cities are engines of growth and prosperity, which facilitate industries to grow jobs, services and innovations. Cities are also fundamental to lifting people out of poverty through increased employment opportunities and incomes to citizens. No country has reached middle income status without urbanizing. That being said, the way that cities urbanize is important to growth, poverty and livability. If adequate investments are not made in basic infrastructure and services, urban planning, and in ensuring a governance and financing structure that can deliver for residents, cities instead can end up with major problems of congestion, pollution, sprawl, and inequality which can create or worsen social divisions, and potentially contribute to crime and violence. The report, Myanmar’s Urbanization: Creating Opportunities for All aims to understand urbanization in Myanmar drawing on the growing literature on the topic in Myanmar, especially for Yangon. It uses an inclusive urbanization lens and proposes a set of priority policy areas for urgent attention that will help to ensure the benefits of urbanization are widely realized given the projected growth of cities. An inclusion lens is particularly important in Myanmar as the country transitions from a complex history that has been characterized by decades of economic and political isolation, conflict, and underdevelopment. Inclusive urbanization is reliant on three keydimensions; economic, social and spatial. Economic inclusion refers to equitable access to employment and income-generating activities in a city, and resilience to shocks. Spatial inclusion refers to equitable and affordable access to land, housing, infrastructure and basic public services. Social inclusion relates to individual and group rights, equity, security and dignity. Such aspects of social inclusion and exclusion are relevant to groups who are often marginalized inday-to-day urban life.